2000
DOI: 10.1016/s1083-8791(00)70027-9
|View full text |Cite
|
Sign up to set email alerts
|

Idiotype vaccination using dendritic cells after autologous peripheral blood progenitor cell transplantation for multiple myeloma

Abstract: The idiotype (Id) determinants on the multiple myeloma immunoglobulin can serve as tumor-specific antigens. An anti-Id immune response may stem the growth of the malignant clone. We report on 26 patients treated at our institution with high-dose chemotherapy and peripheral blood progenitor cell transplantation (PBPCT) and vaccinated with the Id protein. The patients received chemotherapy and PBPCT to establish a minimal residual disease state. After high-dose therapy, the patients received a series of monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…The two patients that developed cellular IR also were in CR after auto-HCT (before vaccination) and they remained in CR at the time of the publication of the report; therefore, the clinical impact of this approach remains to be determined. A larger series of a total of 26 patients had similar results, 59 and other Id-based strategies are under investigation. 60 Rosenblatt et al 61 used DC/PCM cell fusions in the early postauto-HCT setting as additional consolidation.…”
Section: Myeloma Vaccinesmentioning
confidence: 82%
“…The two patients that developed cellular IR also were in CR after auto-HCT (before vaccination) and they remained in CR at the time of the publication of the report; therefore, the clinical impact of this approach remains to be determined. A larger series of a total of 26 patients had similar results, 59 and other Id-based strategies are under investigation. 60 Rosenblatt et al 61 used DC/PCM cell fusions in the early postauto-HCT setting as additional consolidation.…”
Section: Myeloma Vaccinesmentioning
confidence: 82%
“…40,[225][226][227] In some studies, patients also received soluble antigen, 40 complicating evaluation of the response to the idiotype-pulsed DCs. Occasional tumor regressions were observed in some patients with lymphoma.…”
Section: Lymphoma and Myelomamentioning
confidence: 99%
“…Until now, the various studies of DC-based Id vaccination in MM have been reported (Bendandi et al, 2006;Lim & Bailey-Wood, 1999;Liso et al, 2000;Reichardt et al, 2003;Rollig et al, 2011;Titzer et al, 2000;Yi et al, 2002Yi et al, , 2010. Although Id-specific CTLs and immune response could be induced in some patients, clinical responses have been observed rarely in few patients after vaccination (Titzer et al, 2000).…”
Section: Idiotype and Idiotype-pulsed Dcs In MMmentioning
confidence: 99%